PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PREDICT-OBSERVE-EXPLAIN(POE) PADA SUB MATERI SIFAT SENYAWA ION DAN KOVALEN UNTUK KELAS X FARMASI SMK PANCA BAHKTI SUNGAI RAYA - Purwanti Suci Muji Daryamti; Fitriani Fitriani; Raudhatul Fadhilah (Universitas Muhammadiyah Pontianak, 2018)
The development research is initiated by the lack of students’ knowledge in determining the Properties of Ionic and Covalent Compounds, and aimed at designing the student worksheet. Using Research and Development model of 3D (Define, Design, and Develop), this study included validation sheet, teacher and students questionnaires, and pretest posttest as the instruments. The study reveals a number of findings. First, the average score of validation criteria was 99,43% (strongly valid), with an average score of media expert by 89,58% (strongly valid). Second, the results of practicality criteria taken from the students respon were 85,53% (strongly practical), and from the teacher respon was 98 ,75% (strongly practical). Third, the effectiveness criteria of pretest and posttest after taught by Predict-Observe-Explain (POE) worksheet and counted by N-gain was considered very good (0,701). In conclusion, Predict-Observe-Explain (POE) Based Worksheet is effectively used as teaching materials in Properties of Ionic and Covalent Compounds class of the tenth grade students of Pharmacy atPanca Bhakti Vocational School Sungai Raya.Keywords: Students worksheet, Predict-Observe-Explain (POE), Properties of Ionic and Covalent Compound